Програмно-апаратні засоби для проведення ONLINE трансляції - Грицаков, І. В. (ХНУРЕ, 2023)
The last few years have shown that online broadcasts have become very popular in today's world, and this popularity continues to grow. Broadcasts can be used for various purposes: they can be used for live broadcasts of events such as conferences, festivals, exhibitions and sports competitions. They can also be used to showcase products and services, stream video games, stream music and TV shows. Online broadcasts also allow the audience to interact with the content by commenting and asking questions in real time. That is, they are very convenient for conducting online training.
Keywords: ONLINE трансляція